Analisis Faktor-faktor Yang Mempengaruhi Keputusan Nasabah Berasuransi Syariah di Desa Sordang Bolon Kec. Ujung Padang Kab. Simalungun - Yuni, Yuni; Imsar, Imsar; Jannah, Nurul (Journal of Student Development Informatics Management (JoSDIM), 2023)
The purpose of this study is to determine the factors of income, marketing, environment and customer decisions in sharia insurance. The research method used is a quantitative method. And the population is the people in Sordang Bolon Village, Kec. Edge of the district Simalungun. There were 364 people who became the sample of this study using the Slovin formula with a sampling error (0.5) of 5% so that there were 104 respondents. To get the data, use a questionnaire tool. Analysis tests include normality test, multicollinearity test, and heteroscedasticity test. Data analysis techniques include t test, f test, multiple regression and coefficients. The results of this study indicate that the determination (R Square) of the independent variable on the dependent variable is equal to 0.876 which means 87.6%. Based on the income variable (X1) of 0.000, the significance value of tcount <0.05. Based on testing on the marketing variable (X2), which has a tcount of 6.788 > 1.99. The environmental variable (X3) has a p-value of 0.294 <0.05, which means it influences the decisions of sharia-insured customers. This is in accordance with the t value of significance <0.05. This means that simultaneously the factors of income, marketing, environment have a positive effect on the decisions of customers with sharia insurance.